Pojale (Ketela Pohon Jagung dan Kedelai) sebagai Bahan Pengembangan Beras Analog Pengendali Kegemukan - Sukamto Sukamto; Moh. Sui; Sudiyono Sudiyono; Patria Domas G.; Fatimah Karim (Research Center for Suboptimal Lands (PUR-PLSO), Universitas Sriwijaya, 2018)
Sukamto et al, 2018. The Development of Analog Rice as Obesity Control from Pojale Materials (Cassava, Corn and Soybean). JLSO 7(2):128-135.Population growth can cause 2 problems, namely food shortage population and overweight and obese population. Indonesians who are overweight and obese have reached 25%. This study aimed to develop analog rice to control obesity from corn and cassava-based ingredients than contain high amylose, and soybeans as a protein source. Corn flour, cassava flour and soy flour passed the 80-mesh sieve was used in the study. The analog rice granulation process used the Twin Screw Extruder KL Protecal machine. The temperature settings for the extruder thread at the beginning, middle and end were 80, 85 and 90 Â°C, respectively. The results showed that the composition of the ingredients of corn flour, 1:1 cassava flour and without addition of soy flour yielded the best results of analog rice in terms of color, texture, structure and surface smoothness. The analog rice can be cooked for 8-10 minutes with addition of water by 1.5 times of the rice. Cooked rice contained 9.44% protein, 76.40% starch, 7.99% fiber, and 36% amylose when the formula was added with 10% soy flour. Sensory test showed that panelists was on average like the rice.